2021
DOI: 10.3389/fimmu.2020.613007
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/PD-1 Pattern of Expression Within the Bone Marrow Immune Microenvironment in Smoldering Myeloma and Active Multiple Myeloma Patients

Abstract: BackgroundThe PD-1/PD-L1 axis has recently emerged as an immune checkpoint that controls antitumor immune responses also in hematological malignancies. However, the use of anti-PD-L1/PD-1 antibodies in multiple myeloma (MM) patients still remains debated, at least in part because of discordant literature data on PD-L1/PD-1 expression by MM cells and bone marrow (BM) microenvironment cells. The unmet need to identify patients which could benefit from this therapeutic approach prompts us to evaluate the BM expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…MM patients are known to have a deep reduction of CD4 + T cells with an inverted CD4 + /CD8 + ratio compared to precursors stages of the disease. 35 In fact, CD4 + T cells are closely associated with B cell differentiation into IgG-producing plasma cells and with the development of an adequate humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…MM patients are known to have a deep reduction of CD4 + T cells with an inverted CD4 + /CD8 + ratio compared to precursors stages of the disease. 35 In fact, CD4 + T cells are closely associated with B cell differentiation into IgG-producing plasma cells and with the development of an adequate humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…MM patients are known to have a deep reduction of CD4 + T cells with an inverted CD4 + /CD8 + ratio compared to precursors stages of the disease. 28 In fact, CD4 + T cells are closely associated with B cell differentiation into IgG-producing plasma cells and with the development of an adequate humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was an inversion of the CD4+/CD8+ ratio in patients with relapsed MM, followed by increased levels of IL-6 expression. There was a remarkable positive correlation between %CD14+PD-L1+ and %CD8+PD-1+ cells in relapsed patients compared to the patients with SMM and newly diagnosed MM (NDMM) ( 30 ). Therefore, MGUS and MM obviously exhibit the immune yin-yang effects.…”
Section: The Yin and Yang Effects Of Multiple Myeloma Progressionmentioning
confidence: 99%
“…found that as tumor load increases, the quantity of CD16+CD14 dim monocytes has been shown to increase ( 73 ). Meanwhile, another study found that in MM and SMM patients, PD-L1 was expressed at higher levels in CD14+CD16+ monocytes than CD14+CD16- cells, independent of disease stage ( 30 ). Therefore, other types of cells also play an important role in MM progression ( Figure 2 , Table 1 ).…”
Section: The Yin and Yang Effects Of Immune Cells Associated With Mul...mentioning
confidence: 99%